2020
DOI: 10.15641/jarer.v5i1.848
|View full text |Cite
|
Sign up to set email alerts
|

Market Rent Determinants of Residential Apartments in Addis Ababa, Ethiopia

Abstract: Rapid urbanisation and population growth increase the demand for housing. Given its importance to human wellbeing, the right to housing is recognised in international, regional and domestic legislation. The rental housing sector is the major form of housing tenure in Ethiopia. Given financial constraints, Ethiopian tenants tend to rent instead of buying property. However, there are no well-developed procedures that guide how rental value is determined in Ethiopia. As such, the purpose of this study is to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
2
5
2
Order By: Relevance
“…These structural characteristics were found to be statistically significant in influencing the apartment prices in the study area but were omitted in the final model to cure the collinearity problem. However, the findings of the study differ from several existing studies that have established that age, security, access to a balcony, provision of lifts and the entire plot size are important variables influencing apartment values (Abidoye and Chan, 2018;Belete and Yilma (2020); Ferlan et al (2017); Kieti and Ogolla, 2021;Randeniya et al (2017); Oduwole and Eze, 2013, just to mention but a few). The findings of this paper have established that these variables are statistically insignificant in affecting apartment values in the NMA, reinforcing the need for a specific valuation model in a specific property market due to the heterogeneity nature of the real estate and the subjective nature of the consumers' utility.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…These structural characteristics were found to be statistically significant in influencing the apartment prices in the study area but were omitted in the final model to cure the collinearity problem. However, the findings of the study differ from several existing studies that have established that age, security, access to a balcony, provision of lifts and the entire plot size are important variables influencing apartment values (Abidoye and Chan, 2018;Belete and Yilma (2020); Ferlan et al (2017); Kieti and Ogolla, 2021;Randeniya et al (2017); Oduwole and Eze, 2013, just to mention but a few). The findings of this paper have established that these variables are statistically insignificant in affecting apartment values in the NMA, reinforcing the need for a specific valuation model in a specific property market due to the heterogeneity nature of the real estate and the subjective nature of the consumers' utility.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of this paper generally reinforce the consensus that property values are influenced by their internal and external attributes: structural, locational and neighbourhood characteristics (see for example Brett et al, 2003;Kieti and Ogolla, 2021;McCluskey and Borst, 2007;Thanasi, 2016). Several studies, for instance, have found apartment size to be the most significant factor influencing its value positively (see Ahmed and Yacim, 2018;Belete and Yilma (2020);Nguyen, 2020;Randeniya et al (2017);Thanasi, 2016;Sirmans et al, 2005, amongst other studies). Similarly, location (usually measured in distance from the CBD) has been identified by most existing studies as an important variable negatively influencing property values (see for example Ayan and Erkin (2014); Ferlan et al (2017); Frew and Wilson, 2002;McCluskey and Borst, 2007;Randeniya et al (2017); Oduwole andEze, 2013, Ottensmann et al, 2008, amongst others).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations